2022
DOI: 10.1038/s41598-022-08700-4
|View full text |Cite
|
Sign up to set email alerts
|

Systematic and meta-analysis of Mycobacterium avium subsp. paratuberculosis related type 1 and type 2 diabetes mellitus

Abstract: Global increase in diabetes (DM) prevalence necessitated the need to establish the association between DM and environmental triggers including MAP (Mycobacterium avium subsp. paratuberculosis) that have been postulated to play a role in DM etiopathology for effective management. The present investigation aimed to assess the odds ratio (OR) presenting the association between MAP and DM. MAP-related DM studies were systematically retrieved from 6 databases until 31 September 2021 according to PRISMA principles f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 64 publications
0
8
0
Order By: Relevance
“…In Canada, the annual economic impact of JD is estimated at $28 million USD, mainly due to reduced milk production, increased cattle mortality, and the early culling of infected animals ( Rasmussen et al, 2021 ). In addition, this infection has raised concerns, in part due to the possible link between MAP and Crohn’s disease in humans, leading to discussions related to the impact of MAP on chronic diseases and food safety ( Waddell L. A. et al, 2016 ; Kuenstner et al, 2017 ; Agrawal et al, 2021 ; Ekundayo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…In Canada, the annual economic impact of JD is estimated at $28 million USD, mainly due to reduced milk production, increased cattle mortality, and the early culling of infected animals ( Rasmussen et al, 2021 ). In addition, this infection has raised concerns, in part due to the possible link between MAP and Crohn’s disease in humans, leading to discussions related to the impact of MAP on chronic diseases and food safety ( Waddell L. A. et al, 2016 ; Kuenstner et al, 2017 ; Agrawal et al, 2021 ; Ekundayo et al, 2022 ).…”
Section: Introductionmentioning
confidence: 99%
“…The statistical program R 4.0.5 packages was used to conduct all analyses with 2-tailed of p -values < 0.05 level of significance [30] . Further, heterogeneity between studies was quantified using Q -statistic and I 2 -statistics at a significant heterogeneity threshold [33] , [34] , [35] .…”
Section: Methods and Search Strategiesmentioning
confidence: 99%
“…T1D is a severe autoimmune condition associated with infant exposure to dietary cow milk (Dow & Alvarez, 2022;Ozana et al, 2022), with the disease high in children worldwide (Ozana et al, 2022). An investigation using meta-analysis found that anti-MAP antibodies and MAP deoxyribonucleic acid (DNA) have a significant link with T1D (Ekundayo et al, 2022b). Association between MAP and T1D has been confirmed using polymerase chain reaction (PCR); by detecting MAP-specific IS900 signature (Sechi et al, 2008;Rosu et al, 2009;Rani et al, 2010;Shariati et al, 2016), immune assay (ELISA); by detecting antibodies against MAP 3865c and ZnT8 homologous epitopes, and the detection of the cell envelope protein (MptD) and immune response to MptD peptide.…”
Section: Tablementioning
confidence: 99%